Georg Steindorff, Heinrich Schäfer und Thomas Mann: Ein neuer Brieffund zu Thomas Manns Beziehungen zu Ägyptologen anlässlich seines Joseph-Romans - Kern, Susanne Voss (Zeitschrift für ägyptische Sprache und Altertumskunde, 2016)
The discovery of a letter written on 12 th August 1943 by Thomas Mann to Georg Steindorff provides new insights about the contacts of the author of the ‘Joseph’ novels to Egyptologists. These were not limited to his pre-emigration Munich environment and his acquaintance with Wilhelm Spiegelberg, as previously thought, but also included Heinrich Schäfer who probably contributed to Mann’s conception of the tetralogy. The author’s letter to Steindorff, post-dating the completion of the final volume in the series, is the first evidence of any connection between them.